2019
DOI: 10.1093/cvr/cvz214
|View full text |Cite
|
Sign up to set email alerts
|

Preventing treatment failures in coronary artery disease: what can we learn from the biology of in-stent restenosis, vein graft failure, and internal thoracic arteries?

Abstract: Coronary artery disease (CAD) remains one of the most important causes of morbidity and mortality worldwide, and the availability of percutaneous or surgical revascularization procedures significantly improves survival. However, both strategies are daunted by complications which limit long-term effectiveness. In-stent restenosis (ISR) is a major drawback for intracoronary stenting, while graft failure is the limiting factor for coronary artery bypass graft surgery (CABG), especially using veins. Conversely, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 184 publications
0
43
0
4
Order By: Relevance
“…Vascular injury is considered to be the main cause of neointimal hyperplasia initiation and progression [27]. Although current strategies to prevent restenosis are focused on the inhibition of neointimal hyperplasia through drugeluting stents and vascular brachytherapy, restenosis rates following endovascular intervention remain high [22,28]. Thus, it is important to understand the molecular mechanisms involved in neointima formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular injury is considered to be the main cause of neointimal hyperplasia initiation and progression [27]. Although current strategies to prevent restenosis are focused on the inhibition of neointimal hyperplasia through drugeluting stents and vascular brachytherapy, restenosis rates following endovascular intervention remain high [22,28]. Thus, it is important to understand the molecular mechanisms involved in neointima formation.…”
Section: Discussionmentioning
confidence: 99%
“…The pelleted exosomes were resuspended in 200 μL of phosphate buffered saline solution (PBS) and quantified by BCA protein assay kit (R33200, Thermo Fisher, USA). Exosomes were then assessed by transmission electron microscopy (TEM) and nanoparticle tracking analysis (NTA), as per previously described protocols [21,22]. Exosomes were further verified by western blot analysis of exosome-associated markers including CD81, CD63, HSP70, Calnexin and TSG101.…”
Section: Isolation and Characterization Of Mesenchymal Stem Cellderivmentioning
confidence: 99%
“…We speculated the mechanism of re-ISR may be similar to that of ISR. Neointimal formation related to proliferation and migration of vascular smooth muscle cells may be a factor 43–46. It is often complicated by elastic recoil of the vessel wall after endovascular angioplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, biological studies of ISR have shown that NF-kB/p65 pathway plays a significant role in the overexpression of VCAM-1 and E-selectin following stent implantation [103]. In human studies, it was found that, following a decrease in NF-kB/p65 translocation, the expression of VCAM-1, E-selectin, and endothelial cell activation also diminished dramatically.…”
Section: Discussionmentioning
confidence: 99%